Bletilla striata polysaccharide composite membrane as well as preparation method and application thereof
By using composite membranes of white polysaccharide, sodium alginate and sodium carboxymethylcellulose, the problem of non-biodegradation of food packaging materials is solved, and efficient fruit and vegetable preservation and environmentally friendly packaging solutions are achieved.
Patent Information
- Application Number
- CN202411065024.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-20
AI Technical Summary
Existing food packaging materials are not biodegradable, resulting in environmental pollution and garbage disposal problems, and it is difficult to effectively extend the shelf life of fruits and vegetables.
White and polysaccharides are used as film forming substrates, combined with sodium alginate and sodium carboxymethylcellulose, and a white and polysaccharide composite film with good performance is prepared by blending and casting method for food packaging.
The prepared white and polysaccharide composite membrane has good mechanical properties, low water vapor transmission rate and antibacterial effects, which can effectively extend the shelf life of strawberries, reduce the rot rate and water loss rate, and increase the commodity value of food.
Smart Images

Figure CN119161610A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of food packaging materials, and more specifically, relates to a Bletilla striata polysaccharide composite film and a preparation method and application thereof. Background Art
[0002] Petroleum-based polymers and plastic products are widely used in the food packaging market because they are not only more affordable but also more convenient. However, non-biodegradable and non-renewable are the fatal disadvantages of these polymers. With the intensification of "white pollution", it is urgent to study new packaging methods for food packaging. With the improvement of people's quality of life and the continuous increase in health awareness, natural products have gradually entered people's field of vision. Understanding the functions of natural active factors and further applying them to the food field has developed into one of the mainstream trends.
[0003] Due to their high water content, fruits and vegetables will quickly deteriorate, rot and develop a poor appearance after being harvested. In order to improve the storage quality and food safety of fruits and vegetables, people have adopted a variety of preservation strategies such as cold chain, modified atmosphere packaging, modified atmosphere storage, active packaging, and edible packaging. Among them, edible packaging is a thin layer formed directly on the surface of food (edible coating), or a film formed separately and then wrapped on the surface of food (edible film). Since it can be eaten with the food it contains, there is no need to consider garbage disposal in this situation. Even if we do not directly eat edible packaging materials, its degradation rate is better than other synthetic and biodegradable packaging materials. In this way, we also reduce the cost of landfill and give full play to limited manpower and material resources. Based on this, the use of natural polymer materials to prepare edible packaging films to replace synthetic plastic packaging has become an important trend in the food packaging industry and is also the key to solving food safety issues.
[0004] Bletilla striata is a perennial herb and a traditional Chinese herbal medicine. Its dried tubers are used as medicine. The Chinese Pharmacopoeia stipulates that Bletilla striata has the effects of hemostasis, antibacterial, detumescence, healing and enhancing body functions. It not only has high ornamental value, but also has good economic value. Bletilla striata polysaccharide is the main component of Bletilla striata tissue, which mainly plays a biologically active role. The main component of Bletilla striata polysaccharide is a large molecular heteropolysaccharide with a complex structure. It has biological activities such as antioxidant activity, prolonged fruit and vegetable preservation, antibacterial and good biocompatibility. In recent years, the application research of Bletilla striata polysaccharide has gradually attracted the attention of researchers and entered people's field of vision, but it still has some defects that need to be solved. Summary of the invention
[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0006] In order to achieve these purposes and other advantages of the present invention, a method for preparing a polysaccharide composite film of Bletilla striata is provided, comprising the following steps:
[0007] Step 1, preparing Bletilla striata powder;
[0008] Step 2, preparing Bletilla striata polysaccharide;
[0009] Step 3, dissolving Bletilla striata polysaccharide, sodium alginate and sodium carboxymethyl cellulose in deionized water respectively, stirring in a water bath, to prepare Bletilla striata polysaccharide solution, sodium alginate solution and sodium carboxymethyl cellulose solution respectively;
[0010] Step 4: Evenly mix the three solutions obtained in step 3 to obtain a mixed solution, then add glycerol, stir in a water bath, and after ultrasonic degassing, pour the obtained film-forming solution into a mold and evenly cast it. After drying, peel off the film to obtain a Bletilla striata polysaccharide composite film.
[0011] Preferably, in the step 1, the preparation method of the Bletilla striata powder is: wash the Bletilla striata root tubers, freeze them at -15 to -20°C for 3 to 6 hours, then crush the Bletilla striata root tubers at a crushing temperature of -15 to -20°C and a pressure of 0.1 to 0.3 MPa, spray dry, and pass through a 100-mesh sieve to obtain the Bletilla striata powder.
[0012] Preferably, in the step 2, the preparation method of Bletilla striata polysaccharide is as follows: add Bletilla striata powder to pure water, stir at 70-90°C and 300-600rpm for 1-2h, then centrifuge at 2000-4000rpm for 8-15min, collect the supernatant, add the remaining insoluble residue into pure water again, stir and centrifuge twice, combine the supernatants collected three times, evaporate and concentrate in a water bath, then add 2-4 times the volume of 95% ethanol, stir into flocs and let stand at 2-6°C for 10-14h, then centrifuge at 4000-6000rpm for 8-15min, collect the precipitate, freeze for 10-14h, then freeze-dry, and crush at 10000rpm for 3min to obtain Bletilla striata polysaccharide.
[0013] Preferably, the mass volume ratio of the Bletilla striata powder to pure water is 3-6 g:100-300 mL; the water bath temperature is 50-60° C., and the volume is evaporated and concentrated to 1 / 10-2 / 5.
[0014] Preferably, in step three, the concentration of the Bletilla striata polysaccharide solution is 1.4-1.6wt%; the concentration of the sodium alginate solution is 1.0-1.2wt%; and the concentration of the sodium carboxymethylcellulose solution is 1.2-1.6wt%.
[0015] Preferably, the concentration of the Bletilla striata polysaccharide solution is 1.6wt%; the concentration of the sodium alginate solution is 1.2wt%; and the concentration of the sodium carboxymethylcellulose solution is 1.6wt%.
[0016] Preferably, in step 3, the stirring temperature in the water bath is 50 to 70° C. and the stirring time is 1 to 3 hours.
[0017] Preferably, in step 4, the amount of glycerol added is 0.5-1.0 wt% of the mixed solution; the temperature of water bath stirring is 50-70° C., and the time is 20-40 min; and the drying temperature is 50-60° C., and the time is 20-30 h.
[0018] Preferably, in the step three, the preparation method of the Bletilla striata polysaccharide solution is replaced by: dissolving Bletilla striata polysaccharide in deionized water, adding tannic acid and sodium stearate, stirring in a water bath, and obtaining a Bletilla striata polysaccharide solution; wherein the concentration of Bletilla striata polysaccharide in the Bletilla striata polysaccharide solution is 1.4-1.6wt%, and the mass ratio of Bletilla striata polysaccharide, tannic acid and sodium stearate is 1-2:0.1-0.5:0.01-0.1.
[0019] Preferably, in step 4, the obtained mixed solution is added to an ultra-high pressure microfluidizer and treated at a pressure of 100 to 300 MPa for 2 to 5 times.
[0020] A Bletilla striata polysaccharide composite film is prepared by the above preparation method.
[0021] Application of the Bletilla striata polysaccharide composite film prepared by the preparation method described above in inhibiting Escherichia coli and Staphylococcus aureus.
[0022] Application of the Bletilla striata polysaccharide composite film prepared by the preparation method as described above in strawberry preservation.
[0023] The present invention includes at least the following beneficial effects: The present invention provides a Bletilla striata polysaccharide composite film, which uses Bletilla striata polysaccharide as a film-forming substrate, glycerol as a plasticizer, and sodium alginate and sodium carboxymethyl cellulose are added, and a ternary composite film with good performance is prepared by a blending and casting method. The components in the film-forming material of the present invention are evenly distributed and hydrogen bonding exists. The obtained Bletilla striata polysaccharide composite film has a stable structure, good compatibility between molecules, good mechanical properties and low water vapor permeability, and has a certain inhibitory effect on Escherichia coli and Staphylococcus aureus.
[0024] In addition, the present invention evaluates the preservation effect of strawberries through the composite film, providing a reference for the development and application of the Bletilla striata polysaccharide composite film in food packaging. The Bletilla striata polysaccharide composite film of the present invention has an excellent preservation effect, can reduce the water loss rate and decay rate of strawberries, prolong the preservation effect of strawberries, increase the commodity value of strawberries, and extend the shelf life.
[0025] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A is the XRD diagram of the Bletilla striata polysaccharide film, sodium alginate film, and sodium carboxymethyl cellulose film prepared in Comparative Examples 8-10, Figure 1 B is the XRD pattern of the Bletilla striata polysaccharide composite film prepared in Example 1 and the binary composite film prepared in Comparative Example 7;
[0027] Figure 2 This is a surface SEM image of the Bletilla striata polysaccharide composite film prepared in Example 1;
[0028] Figure 3 This is a cross-sectional SEM image of the Bletilla striata polysaccharide composite film prepared in Example 1;
[0029] Figure 4 The antibacterial performance of the Bletilla striata polysaccharide composite film prepared in Example 1 against Escherichia coli;
[0030] Figure 5 The antibacterial performance of the Bletilla striata polysaccharide composite film prepared in Example 1 against Staphylococcus aureus;
[0031] Figure 6 The inhibition zones of the Bletilla striata polysaccharide composite film prepared in Example 1, the binary composite film prepared in Comparative Example 7, and the Bletilla striata polysaccharide film prepared in Comparative Example 10 against Escherichia coli;
[0032] Figure 7 The inhibition zones of the Bletilla striata polysaccharide composite film prepared in Example 1, the binary composite film prepared in Comparative Example 7 and the Bletilla striata polysaccharide film prepared in Comparative Example 10 against Staphylococcus aureus;
[0033] Figure 8 The effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the protein concentration in the Escherichia coli bacterial solution;
[0034] Fig. 9 The effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the protein concentration in the Staphylococcus aureus liquid;
[0035] Fig.10 The effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the permeability of Escherichia coli cell membrane;
[0036] Fig.11 The effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the cell membrane permeability of Staphylococcus aureus;
[0037] Fig.12The effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the permeability of the Escherichia coli cell wall;
[0038] Fig.13 The effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the cell wall permeability of Staphylococcus aureus;
[0039] Fig.14 The appearance changes and decay degree of strawberries packaged in CK group, PE group, coating group and film-coated group after 7 days of storage;
[0040] Fig.15 The weight loss rate of strawberries packaged in CK group, PE group, coating group and film-coated group during storage;
[0041] Fig.16 The graphs of the changes in respiration intensity during storage of strawberries packaged in CK group, PE group, film coating group and film encapsulation group;
[0042] Fig.17 The graphs showing the changes in soluble solids content during storage of strawberries packaged in CK group, PE group, coating group and film-coated group;
[0043] Fig.18 The graphs showing the changes in titratable acid content during storage of strawberries packaged in CK group, PE group, film coating group and film encapsulation group;
[0044] Fig.19 The graphs of ascorbic acid content changes during storage of strawberries packaged in CK group, PE group, film coating group and film encapsulation group;
[0045] Fig. 20 This is a graph showing changes in malondialdehyde content in strawberries packaged in CK group, PE group, coating group and encapsulated group during storage. DETAILED DESCRIPTION
[0046] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0047] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0048] Example 1
[0049] A method for preparing a Bletilla striata polysaccharide composite film comprises the following steps:
[0050] Step 1: Wash the root tubers of Bletilla striata, freeze them at -15°C for 4h, then crush the root tubers of Bletilla striata at a crushing temperature of -15°C and a pressure of 0.1MPa, spray dry, and pass through a 100-mesh sieve to obtain Bletilla striata powder;
[0051] Step 2: Add 5 g of Bletilla striata powder to 200 mL of pure water, stir at 80°C and 500 rpm for 1 hour, then centrifuge at 3000 rpm for 10 minutes, collect the supernatant, add the remaining insoluble residue into pure water again, stir and centrifuge twice, combine the supernatants collected three times, evaporate and concentrate to 1 / 5 volume in a 55°C water bath, then add 3 times the volume of 95% ethanol, stir into floccules and let stand at 4°C for 12 hours, then centrifuge at 5000 rpm for 10 minutes, collect the precipitate, freeze it in a refrigerator for 12 hours, then freeze-dry it in a freeze dryer, crush it at 10000 rpm for 3 minutes to obtain Bletilla striata polysaccharide, and store it in a glass vacuum desiccator;
[0052] Step 3, dissolving R. rubrum polysaccharide (RBP), sodium alginate (SA), and sodium carboxymethyl cellulose (CMC) in 100 mL of deionized water, respectively, and stirring in a 60° C. water bath for 2 h to fully dissolve, to prepare a R. rubrum polysaccharide solution with a concentration of 1.6 wt%, a sodium alginate solution with a concentration of 1.2 wt%, and a sodium carboxymethyl cellulose solution with a concentration of 1.6 wt%;
[0053] Step 4: Evenly mix the three solutions prepared in step 3 to obtain a mixed solution, then add 0.5wt% of glycerol to the mixed solution, stir in a water bath at 60°C for 30 minutes, and after ultrasonic degassing, pour the obtained film-forming solution into a culture dish with a diameter of 10 cm and evenly cast it. After drying at 55°C for 24 hours, remove the film to obtain a Bletilla striata polysaccharide composite film, which is stored in a sealed bag.
[0054] Embodiment 2-5
[0055] In Examples 2-5, the concentrations of the Bletilla striata polysaccharide solution, the sodium alginate solution and the sodium carboxymethyl cellulose solution, and the amount of glycerol added are as shown in Table 1, and the remaining steps are the same as in Example 1.
[0056] Table 1
[0057] wt% Bletilla striata polysaccharide Sodium alginate Sodium Carboxymethyl Cellulose glycerin Example 1 1.6 1.2 1.6 0.5 Example 2 1.6 1.2 1.2 0.5 Example 3 1.6 1.0 1.6 0.5 Example 4 1.4 1.2 1.4 0.5 Example 5 1.6 1.2 1.2 1.0
[0058] Comparative Examples 1-6
[0059] In Comparative Examples 1-6, the concentrations of the Bletilla striata polysaccharide solution, the sodium alginate solution and the sodium carboxymethyl cellulose solution, and the amount of glycerol added are as shown in Table 2, and the remaining steps are the same as in Example 1.
[0060] Table 2
[0061]
[0062]
[0063] Determination of mechanical properties of composite films: tensile strength and elongation at break were measured according to the method of VUDDANDA et al. (Vuddanda PR, Montenegro-Nicolini M, Morales JO, et al. Effect of plasticizers on the physico-mec hanical properties of pullulan based pharmaceutical oral films [J]. European Journal of Ph armaceutical Sciences, 2017, 96: 290-298.) and improved, and measured using an electronic universal material testing machine. The prepared composite film material was peeled off and cut into 80mm×10mm strips for standby use. The clamping distance of the universal material testing machine was set to 40mm, and the tensile rate was set to 50mm / min. Then the two ends of the sample were fixed at the two ends of the clamping distance, and the test was carried out. The tensile strength and elongation at break were calculated according to the following formulas:
[0064]
[0065] Wherein: TS is the tensile strength, MPa; F is the tensile force when the sample breaks, N; L is the average thickness of the composite film, mm; W is the width of the film sample, mm.
[0066]
[0067] Wherein: EAB is the elongation at break, %; L0 is the length of the clamp distance set for the test, mm; L1 is the length of the clamp distance when the film sample breaks, mm.
[0068] Determination of water vapor permeability of composite film: Refer to the method of Chen Luzhu et al. (Preparation of pullulan / carboxymethyl chitosan composite film and its preservation effect on Macrobrachium rosenbergii [J]. Food and Fermentation Industries, 2021, 47(24): 137-143) for determination. 20 mL of pure water was dripped into a 50 mL beaker, and the mouth of the cup was covered and fixed with the prepared composite film without leaving any gaps. The beaker was placed in a desiccator filled with silica gel at the same temperature of 22 °C. Three parallel samples were selected for each group of composite film samples and weighed every 2 hours. After distilled water was poured into the cup, the mouth of the cup was wrapped with a composite film and fixed with a rubber ring. At room temperature, it was placed in a desiccator with silica gel at the bottom. The water vapor permeability of the composite film is calculated according to the following formula:
[0069]
[0070] Where: WVP is the water vapor transmission coefficient, g·mm / m2 ·h·Kpa; Δm is the weight change of the weighing bottle, mg; x is the film thickness, mm; S is the film area, m 2 ; t is the interval time, h; ΔP is the pressure difference on both sides of the membrane, Pa.
[0071] The Bletilla striata polysaccharide composite films of Examples 1-5 and Comparative Examples 1-5 were tested, and the results are shown in Table 3. Comprehensive analysis of the tensile strength, elongation at break and water vapor permeability of the composite films shows that Example 1 of the present invention is the optimal formula, that is, the optimal formula of Bletilla striata polysaccharide / sodium alginate / sodium carboxymethyl cellulose is 1.6wt% of Bletilla striata polysaccharide, 1.2wt% of sodium alginate, 1.6wt% of sodium carboxymethyl cellulose and 0.5wt% of glycerol.
[0072] It can be seen from Example 5 and Comparative Examples 2-3 that the continuous increase of Bletilla striata polysaccharide increases the tensile strength of the composite film. This is because Bletilla striata polysaccharide is the main film-forming substrate of the composite film. With the addition of Bletilla striata polysaccharide, the number of molecules increases continuously. As a multi-hydrogen-based natural macromolecule, Bletilla striata polysaccharide undergoes strong hydrogen bonding. The internal structure of the composite film fills the internal pores with the addition of Bletilla striata polysaccharide solution, thus becoming tighter, and the mechanical properties of the composite film are improved. The elongation at break of the composite film increases first and then decreases with the continuous addition of Bletilla striata polysaccharide, because the denser the structure of the composite film, the stronger its mechanical properties. However, when the amount of Bletilla striata polysaccharide added is too high, the brittleness of the film increases and the elongation at break decreases. The advantage of a composite film with good water vapor permeability is that it can inhibit oxygen exchange and mass transfer between the atmosphere and food, thereby preventing the deterioration of food samples; when the content of Bletilla striata polysaccharide is low, the moisture barrier properties of other components of the composite film, such as sodium alginate, are poor, so the water vapor permeability is relatively high at this time; as the content of Bletilla striata polysaccharide components in the composite film continues to increase, the water vapor permeability gradually decreases, which may be because the increase in Bletilla striata polysaccharide molecules per unit volume makes the hydrogen bonding between each other or within itself stronger, thereby reducing the spacing between molecules and increasing the density of its structure.
[0073] From Examples 1, 3, and Comparative Examples 2, 4, and 6, it can be seen that the elongation at break of the composite film increases with the increase of sodium alginate and then tends to be stable. That is because as the concentration of sodium alginate increases, the film-forming components of sodium alginate in the composite film gradually increase, and the unit molecular force between the internal structures of sodium alginate as a thickener is enhanced, the structure is tight, and the thickness of the prepared composite film material gradually increases. However, sodium alginate and CMC are both macromolecular substances with similar structures. As the amount of addition continues to increase, the amount of sodium alginate added as a thickener will make the texture loose, the film-forming property decreases, and the film liquid is too viscous, which will make degassing difficult and the film formation uneven, resulting in a decrease in tensile strength. The dense structure composed of the hydrogen bonding inside the unit molecule of sodium alginate can enhance the mechanical properties of the composite film, but it is not the more the better. When the addition amount of sodium alginate, the film-forming component of the composite film, reaches a saturated state, the mechanical action also tends to a flat state. When the content of sodium alginate increases, the concentration of the film-forming liquid increases, and the water vapor permeability of the prepared composite film also gradually decreases. Because the stronger the unit molecular force between the internal structures of sodium alginate, the tighter the internal structure of the composite membrane, the smaller the water vapor permeability.
[0074] From Examples 1-2 and Comparative Examples 1-2, it can be seen that at an appropriate concentration, the combination of sodium carboxymethyl cellulose and polysaccharides can increase the synergistic effect of the composite film packaging material, making the internal structure of the film-forming material more stable, thereby increasing the mechanical properties of the film. When the sodium carboxymethyl cellulose content in the film-forming liquid is too high, with the combination of sodium carboxymethyl cellulose and sodium alginate, the film liquid will become more viscous, the fluidity will deteriorate, the dissolution time will be longer, and the bubbles in the film liquid after ultrasonic degassing are still difficult to discharge, affecting the mechanical properties of the film. The water vapor permeability of the composite film shows a decreasing trend with the increase in the amount of sodium carboxymethyl cellulose added. When sodium carboxymethyl cellulose and sodium alginate are combined, the force between the unit molecules is enhanced, the structure inside the composite film is more compact, and the water vapor transmission rate is reduced.
[0075] As can be seen from Example 4 and Comparative Examples 1 and 5, when the addition of glycerol in the film-forming liquid increases continuously, the tensile strength of the composite film decreases continuously. This is because when the addition of glycerol is less in the prepared film-forming material, the composite film presents a relatively brittle characteristic and has poor flexibility. However, the gradual increase in the addition of glycerol strengthens the molecular action between the material components, thereby suppressing the hydrogen bonding between several macromolecular compounds, and its flexibility is strengthened, and the transparency increases, so the elongation at break is better, and the tensile strength gradually weakens. Glycerol, as a plasticizer, can increase the elasticity and ductility of the film. Since glycerol itself is a small molecule structure with three hydroxyls, it has a strong hydrophilicity, and the pores of the composite film prepared after blending with other film-forming components increase, so water vapor can be enhanced with the increase of pores. The more glycerol content, the more the composite film is soft, and the elasticity of the composite film increases, while the tensile strength decreases, thereby the water vapor permeability increases.
[0076] Table 3
[0077]
[0078] Comparative Example 7
[0079] In this comparative example, no Bletilla striata polysaccharide was added, and the remaining steps were the same as those in Example 1 to prepare a binary composite membrane of sodium alginate and sodium carboxymethyl cellulose.
[0080] Comparative Example 8
[0081] In this comparative example, no Bletilla striata polysaccharide and sodium alginate were added, and the remaining steps were the same as those in Example 1 to prepare a sodium carboxymethyl cellulose film.
[0082] Comparative Example 9
[0083] In this comparative example, no Bletilla striata polysaccharide and sodium carboxymethyl cellulose were added, and the remaining steps were the same as those in Example 1 to prepare a sodium alginate film.
[0084] Comparative Example 10
[0085] In this comparative example, sodium alginate and sodium carboxymethyl cellulose were not added, and the remaining steps were the same as those in Example 1 to prepare a Bletilla striata polysaccharide film.
[0086] The films prepared in Example 1 and Comparative Examples 7-10 were measured by XRD to test their crystallinity. The test conditions were: scanning range 5-40°, voltage 40 kV, current 50 mA, and Cu targeted radiation source. Figure 1 As shown, Figure 1 A is the XRD pattern of Bletilla striata polysaccharide film, sodium alginate film, and sodium carboxymethyl cellulose film. Figure 1 B is the XRD diagram of the Bletilla polysaccharide composite film and the binary composite film. The performance of the composite film is affected by the interaction between the molecules of the material. The strong crystallinity and high density are caused by the interaction between molecules or within molecules. Figure 1 As can be seen in A, RBP has weak crystallinity, sodium alginate film has characteristic diffraction peaks of crystalline structure at 2θ=13.6° and 2θ=21°, and sodium carboxymethyl cellulose film has diffraction peaks of crystalline structure at 2θ=21° and 2θ=15.5°. Assuming that there is no interaction between the structures of the film-forming components of the composite film, the result presented by the diffraction spectrum is the separate crystalline area of each material, or the superposition of the components in the composite film. Figure 1 As shown in B, the strong diffraction peak of the composite film at 2θ=21° originally belongs to the crystallization area of sodium alginate and sodium carboxymethyl cellulose, and now forms a broad diffraction peak with reduced intensity. The above results show that the film-forming components of the Bletilla striata polysaccharide composite film prepared by the present invention have good compatibility.
[0087] The prepared composite film material was dried at a high temperature of 105°C±2°C to keep the quality constant; the prepared composite film packaging material was cut into 1*6mm strips and put into a mortar; liquid nitrogen was used to quickly freeze and quench it, and it was gold-plated; the surface and cross-section of the film were observed at a voltage of 15Kv for microscopic analysis. Figure 2 This is a surface SEM image of the Bletilla striata polysaccharide composite film prepared in Example 1 of the present invention. Figure 3 The cross-sectional SEM image of the Bletilla striata polysaccharide composite film prepared in Example 1 of the present invention. It can be seen that the surface of the Bletilla striata polysaccharide composite film is dense and uniform, with few impurities, indicating the high compatibility between the film-forming components; the cross-sectional structure of the Bletilla striata polysaccharide composite film is relatively tight, the lines are relatively regular, there is no obvious visible phase separation feature and the cross-sectional pore distribution is more uniform, the pores are relatively small, resulting in a double helix conformation and a strong three-dimensional network structure in the film-forming process, and these results can be verified with the results of WVP, TS and EAB. It can be seen from this that the force between the film-forming components of the Bletilla striata polysaccharide composite film of the present invention is strong, a tight structure is formed inside, and it has good compatibility, thereby showing good performance.
[0088] Determination of antibacterial properties of composite films:
[0089] (1) Refer to Zhang Shen (Zhang Shen. Preparation and performance research of edible antibacterial composite film based on sodium alginate [D]. Heilongjiang: Harbin Institute of Technology, 2018.) The method of liquid culture medium was slightly modified and antibacterial test was carried out. Staphylococcus aureus and Escherichia coli were selected as the antibacterial test bacteria. The prepared liquid culture medium was placed in a high-pressure steam sterilizer for sterilization, and the prepared composite film materials were cut into 3×3 cm strips and placed in the liquid culture medium. Then the sterilized nutrient broth was divided into 50 mL flasks, 20 mL of nutrient broth was added, and 10 6 100 μL of culture of CFU / mL bacteria was placed in the broth, and the membrane sample was placed in it and incubated in a constant temperature incubator at 37°C. 1 mL of the broth containing the bacterial culture was taken out every four hours, and the optical density was measured at 560 nm using a spectrophotometer. At the same time, a blank control group was used without any membrane sample.
[0090] (2) The antibacterial activity of the composite membrane against Escherichia coli and Staphylococcus aureus was characterized by using the solid culture medium "inhibition zone method" (Lu Junyu, Zhu Rui, Wu Hejun, et al. Effect and characterization of tea polyphenols on the performance of edible potato starch / sodium alginate composite membrane [J]. Journal of Nuclear Agricultural Sciences, 2020, 34(10): 2226-2234.). Staphylococcus aureus and Escherichia coli were activated and diluted into a test bacterial suspension to be used. The antibacterial activity of the composite membrane was tested by solid and liquid culture tests. The prepared composite membrane samples were cut into small discs with a diameter of about 5 mm and placed on a clean bench for ultraviolet sterilization. After the culture medium was prepared according to the solid culture medium method, 0.2 mL of bacterial suspension was taken on the clean bench and evenly spread on the surface of the solid culture medium. Then the sterilized membrane sample disc was placed on the solid culture medium evenly spread with bacterial suspension, and inverted and cultured in a constant temperature incubator at 37°C for 2 h before testing. The diameter of the inhibition zone of the composite film was measured using a vernier caliper. Each group of samples was tested at least 3 times, and the results were expressed as mean ± standard deviation.
[0091] (3) The effect of the composite membrane on the protein concentration in the culture medium of Escherichia coli and Staphylococcus aureus was determined by referring to the method of Dai Jianli et al. (Dai Jianli, Zhou Sidi, Liu Mingxuan, et al. Study on the antibacterial effect of Bletilla striata polysaccharide [J]. Anhui Agricultural Science Bulletin, 2015, 21(19): 19-21.). The prepared liquid culture medium was placed in a high-pressure steam sterilizer for sterilization, and the prepared composite membrane was cut into 6×6 cm strips and placed in the liquid culture medium. Then the sterilized nutrient broth was divided into 50 mL flasks, 25 mL of nutrient broth was added, and 10 6 100 μL of culture of CFU / mL bacteria was placed in the broth, and the membrane sample was placed in it and incubated in a constant temperature incubator at 37°C. The broth containing the bacterial culture was taken out every 4 hours to determine its protein content, and a blank control test was performed at the same time.
[0092] (4) The effect of the composite membrane on the cell membrane permeability of Escherichia coli and Staphylococcus aureus was determined by referring to the method of Dai Jianli et al. (Dai Jianli, Zhou Sidi, Liu Mingxuan, et al. Study on the antibacterial effect of Bletilla striata polysaccharide [J]. Anhui Agricultural Science Bulletin, 2015, 21(19): 19-21.). The prepared liquid culture medium was placed in a high-pressure steam sterilizer for sterilization, and the prepared composite membrane material was cut into 6×6 cm strips and placed in the liquid culture medium. Then the sterilized nutrient broth was divided into 50 mL flasks, 25 mL of nutrient broth was added, and 10 6 100 μL of culture of CFU / mL bacteria was placed in the broth, and the membrane sample was placed in it and incubated in a constant temperature incubator at 37°C. The broth containing the bacterial culture was taken out every 4 hours to measure the conductivity of the bacterial solution, and a blank control test was performed at the same time.
[0093] (5) The effect of the composite membrane on the cell wall permeability of Escherichia coli and Staphylococcus aureus was determined by referring to the method of Dai Jianli et al. (Dai Jianli, Zhou Sidi, Liu Mingxuan, et al. Study on the antibacterial effect of Bletilla striata polysaccharide [J]. Anhui Agricultural Science Bulletin, 2015, 21(19): 19-21.). The prepared liquid culture medium was placed in a high-pressure steam sterilizer for sterilization and then cut into 6×6 cm strips and placed in the liquid culture medium. The sterilized nutrient broth was then divided into 50 mL flasks, and 25 mL of nutrient broth was placed in a flask containing 10 6 100 μL of the culture of CFU / mL bacteria was placed in the broth, and the membrane sample was placed in it and incubated in a constant temperature incubator at 37°C. Every 4 hours, a portion of the test broth was centrifuged for 10 minutes and the supernatant was taken. The alkaline phosphatase content was determined by an enzyme marker, and DEA was the enzyme activity unit. A blank control test was also performed.
[0094] The antibacterial effect of the Bletilla striata polysaccharide composite film prepared in Example 1 under liquid culture medium test is as follows Figure 4 and Figure 5 As shown, it can be seen that compared with the bacterial growth without membrane, the liquid culture medium with the addition of composite membrane samples has different degrees of inhibition on Escherichia coli and Staphylococcus aureus after 12 hours.
[0095] The results of the inhibition zone method test of the Bletilla striata polysaccharide composite film prepared in Example 1, the binary composite film prepared in Comparative Example 7, and the Bletilla striata polysaccharide film prepared in Comparative Example 10 are as follows: Figure 6 and Figure 7 The diameter of the inhibition zone is shown in Table 4. It can be seen that the composite film has an obvious effect on the diameter of the inhibition zone. The three film-forming materials have different degrees of inhibition on Escherichia coli and Staphylococcus aureus, but the diameter of the inhibition zone of the composite film with Bletilla striata polysaccharide added is significantly better than that of other samples. Bletilla striata polysaccharide can slow down the growth of microorganisms, enrich the application range of Bletilla striata polysaccharide to a certain extent, and improve the antibacterial effect of Bletilla striata polysaccharide composite film.
[0096] Table 4
[0097]
[0098] Effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the protein concentration in the bacterial solution Figure 8 and Fig. 9 It can be seen that compared with the blank control group, after the composite membrane was added to the liquid culture medium, the protein content of the bacterial liquid showed a continuous upward trend. This may be because the macromolecular substances in the cells of Escherichia coli and Staphylococcus aureus seeped through the cell wall and cell membrane, causing cell metabolism disorders.
[0099] Effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the permeability of bacterial cell membranes Fig.10 and Fig.11 As shown. It can be seen that compared with the blank control group, with the extension of culture time, the cell membrane permeability of the liquid culture medium with the addition of the composite membrane showed a gradual upward trend, and was higher than that of the control group. This may be because the bacterial solution with the addition of the composite membrane caused the ion exudation in the cell, damaged the cell membrane, inhibited the bacterial nucleic acid, and increased its permeability.
[0100] Effect of the Bletilla striata polysaccharide composite film prepared in Example 1 on the permeability of bacterial cell walls Fig.12 and Fig.13 As shown. It can be seen that compared with the blank control group, with the extension of the culture time, the alkaline phosphatase content of the bacterial solution in the liquid culture medium containing the composite membrane first increased and then gradually decreased. This may be because the addition of the bacterial solution containing the composite membrane caused the integrity of the cell wall to be destroyed, interfering with the synthesis of the bacterial cell wall, causing cell metabolism disorder and increased permeability.
[0101] Example 6
[0102] A method for preparing a Bletilla striata polysaccharide composite film comprises the following steps:
[0103] Step 1, dissolve sodium alginate and sodium carboxymethyl cellulose in 100 mL of deionized water respectively, stir in a water bath at 60°C for 2 hours to fully dissolve, and prepare a sodium alginate solution with a concentration of 1.2wt% and a sodium carboxymethyl cellulose solution with a concentration of 1.6wt%; dissolve Bletilla striata polysaccharide in 100 mL of deionized water, then add tannic acid and sodium stearate, stir in a water bath at 60°C for 2 hours to fully dissolve, and prepare a Bletilla striata polysaccharide solution; wherein the concentration of Bletilla striata polysaccharide in the Bletilla striata polysaccharide solution is 1.6wt%, and the mass ratio of Bletilla striata polysaccharide, tannic acid and sodium stearate is 1.6:0.2:0.05; the preparation method of Bletilla striata polysaccharide is the same as that in Example 1;
[0104] Step 2: Evenly mix the three solutions prepared in step 1 to obtain a mixed solution, add the mixed solution into an ultra-high pressure microfluidizer, treat it at a pressure of 200 MPa for 3 times, then add 0.5 wt% of glycerol into the mixed solution, stir it in a water bath at 60°C for 30 minutes, and after ultrasonic degassing, pour the obtained film-forming solution into a culture dish with a diameter of 10 cm and evenly cast it, dry it at 55°C for 24 hours, then peel off the film to obtain a Bletilla striata polysaccharide composite film, and store it in a sealed bag.
[0105] In this embodiment, the Bletilla striata polysaccharide solution is modified by adding tannic acid and sodium stearate, and the mixed solution is subsequently treated with ultra-high pressure microfluidization, which is beneficial to the compatibility of Bletilla striata polysaccharide, sodium alginate and sodium carboxymethyl cellulose, enhances the interaction between the film-forming components, improves the stability and uniformity of the Bletilla striata polysaccharide composite film, thereby further improving its mechanical properties, reducing water vapor permeability, and also improving its antibacterial properties.
[0106] Example 7
[0107] In this embodiment, ultrahigh pressure microfluidization treatment is not performed, and the remaining steps are the same as those in Embodiment 6.
[0108] Example 8
[0109] In this embodiment, tannic acid and sodium stearate are not added, and the remaining steps are the same as those in Embodiment 6.
[0110] The tensile strength, elongation at break and water vapor permeability of the Bletilla striata polysaccharide composite films prepared in Example 1 and Examples 6-8 are shown in Table 5, and the diameters of the inhibition zones against Escherichia coli and Staphylococcus aureus are shown in Table 6. It can be seen that the tensile strength, elongation at break and water vapor permeability of Examples 6-8 are better than those of Example 1, and the antibacterial performance is also better than that of Example 1, among which Example 6 is the best.
[0111] Table 5
[0112]
[0113]
[0114] Table 6
[0115]
[0116] Example 9
[0117] A method for preparing a Bletilla striata polysaccharide composite film comprises:
[0118] Step 1, dissolving Bletilla striata polysaccharide, sodium alginate and sodium carboxymethyl cellulose in 400 mL of deionized water respectively, stirring in a water bath at 60° C. for 2 h, to obtain a Bletilla striata polysaccharide solution with a concentration of 1.6 wt %, a sodium alginate solution with a concentration of 1.2 wt % and a sodium carboxymethyl cellulose solution with a concentration of 1.6 wt %; wherein the preparation method of Bletilla striata polysaccharide is the same as that in Example 1;
[0119] Step 2: Evenly mix the three solutions to obtain a mixed solution, then add 0.5wt% of glycerol to the mixed solution, stir in a 60°C water bath for 30 minutes, and after ultrasonic degassing, pour the obtained film-forming solution into a culture dish with a diameter of 20 cm and evenly cast it. After drying at 55°C for 24 hours, remove the film to obtain a Bletilla striata polysaccharide composite film, which is stored in a sealed bag.
[0120] Example 10
[0121] A method for preparing a Bletilla striata polysaccharide composite coating liquid comprises:
[0122] Step 1, dissolving Bletilla striata polysaccharide, sodium alginate and sodium carboxymethyl cellulose in 400 mL of deionized water respectively, stirring in a water bath at 60° C. for 2 h, to obtain a Bletilla striata polysaccharide solution with a concentration of 1.6 wt %, a sodium alginate solution with a concentration of 1.2 wt % and a sodium carboxymethyl cellulose solution with a concentration of 1.6 wt %; wherein the preparation method of Bletilla striata polysaccharide is the same as that in Example 1;
[0123] Step 2: Evenly mix the three solutions to obtain a mixed solution, then add 0.5 wt% of glycerol to the mixed solution, stir in a 60° C. water bath for 30 min, and after ultrasonic degassing, obtain a Bletilla striata polysaccharide composite coating solution.
[0124] Application of Bletilla striata polysaccharide composite film and Bletilla striata polysaccharide composite coating liquid in strawberry preservation:
[0125] 1. Raw materials and reagents
[0126] Strawberries, fresh fruits from the same batch, Longmen Fruit Wholesale Market; phenolphthalein solution, 95% (v / v) ethanol solution, sodium hydroxide solution, oxalic acid solution, 2,6-dichloroindophenol solution, barium chloride solution, trichloroacetic acid solution, thiobarbituric acid solution; all of the above were analytical grade.
[0127] 2. Main instruments
[0128] AR124CN electronic analytical balance, Ohaus Instruments (Shanghai) Co., Ltd.; Dynamica Velocity 14R desktop centrifuge, Qingdao Haosai Technology Co., Ltd.; HT113 handheld refractometer, Tianyuan Technology Co., Ltd.; pHSJ-5 pH meter, produced by Mettler Toledo Instruments; UV-8000S ultraviolet-visible spectrophotometer, Shanghai Yuanxi Instrument Co., Ltd.
[0129] 3. Test methods
[0130] (1) Packaging, processing and storage of strawberries
[0131] Strawberry processing: After purchasing from Longmen Fruit Wholesale Market, strawberries with no mechanical damage, no mold, bright color, uniform maturity and uniform size were selected as test materials and brought back to the laboratory for use on the same day.
[0132] Strawberry storage: The above strawberries were randomly divided into four groups of samples, with three parallels in each group and 10 fruits in each parallel, and stored on trays.
[0133] Coating group: The test objects were packaged with the Bletilla striata polysaccharide composite film prepared in Example 9 and stored at room temperature for later use.
[0134] Coating group: The Bletilla striata polysaccharide composite coating liquid prepared in Example 10 was used, and the test objects were immersed in the Bletilla striata polysaccharide composite coating liquid for 5 minutes, then fished out and naturally dried, and stored at room temperature for later use.
[0135] PE group: The test objects were placed on a tray, sealed with polyethylene plastic wrap and stored at room temperature until use.
[0136] Blank CK group: After the test objects were placed on a tray, they were stored at room temperature until use.
[0137] The weight loss rate, decay degree and weight loss ratio, soluble solids, titratable acid, ascorbic acid and malondialdehyde content, respiration intensity and pH value of the same batch of strawberry samples were determined every 24 hours.
[0138] (2) Sensory measurement
[0139] Sensory quality evaluation: Observe and evaluate the appearance, color, and degree of decay of the selected strawberry samples.
[0140] The decay process of strawberries begins with the surface of the fruit becoming dull and lusterless, followed by the appearance of some white spots on the surface of the fruit. As the storage period increases, the area of the white spots expands, and the surface with mechanical damage begins to rot and mold. Finally, the entire strawberry is completely moldy and moisture from the rotten strawberries appears at the bottom of the container holding the strawberries.
[0141] (3) Determination of weight loss rate
[0142] During the later storage process, the weight of strawberry samples will gradually decrease due to the respiration and transpiration of the fruit after ripening, as well as the extension of storage time. According to the AOAC standard method, strawberry samples under each packaging method are randomly selected and weighed using an electronic balance. The formula for determining the weight loss rate of the samples is as follows:
[0143]
[0144] Where: W1 is the fruit mass before the test, g; W2 is the fruit mass after the test, g.
[0145] (4) Determination of respiratory intensity
[0146] Some fruits and vegetables will produce strong respiration and transpiration after picking, which will lead to fruit ripening. The respiration intensity of such fruits is relatively intense. The stronger the respiration of fruits and vegetables, the faster the nutrients of fruits and vegetables are consumed during the ripening process, and the faster the quality declines. At the same time, the storage period of fruits and vegetables is shorter, which reduces their shelf life and reduces their economic value. The carbon dioxide content produced during the ripening process of fruits and vegetables indirectly reflects the intensity of aerobic and anaerobic conditions of fruits and vegetables. This experiment evaluated and analyzed the respiration intensity of strawberry samples under different packaging methods by using the static method.
[0147] Sample determination method: Place a petri dish at the bottom of the dryer, place 10 mL of 0.4 mol / L NaOH solution, place 50 g of strawberry sample on the partition, seal the petri dish and let it stand for 1 hour. 2 The solution was added to the NaOH solution after standing and phenolphthalein reagent was added, and titrated with oxalic acid solution. The amount of oxalic acid solution used was recorded. Each group of tests was repeated at least three times, and a blank control was also performed. The respiratory intensity calculation method is as follows:
[0148]
[0149] Where: V is the volume of oxalic acid solution consumed by titrating the sample, mL; V0 is the volume of oxalic acid solution consumed by titrating the blank, mL; C is the concentration of oxalic acid solution, mol / L; 44 is CO 2 The molar mass of oxalic acid, g / mol; W is the mass of oxalic acid sample, g; t is the test time, h.
[0150] (5) Determination of pH value
[0151] The method of GB5009.237-2016 "Determination of pH Value of Foods in National Food Safety Standard" was used as a reference and the test was carried out. 5g of strawberry sample was crushed in a beaker, then diluted 10 times with distilled water, filtered to remove large strawberry flesh that was not crushed, and tested with a pH meter at the same time. The same sample under different packaging materials was tested 3 times, and the test results were averaged.
[0152] (6) Determination of soluble solids content
[0153] During the storage process, as the intensity of respiration changes, the sugar inside the fruit is constantly consumed, which is one of the indicators for determining the quality of the fruit. The optical method is used to measure the HT113 handheld refractometer. The specific steps are: centrifuge the quantitatively homogenized strawberry sample, take the supernatant, drop an appropriate amount of the supernatant on the handheld refractometer, observe the data, and record and analyze. Each group of samples is tested 5 times, and the results are averaged.
[0154] (7) Determination of titratable acid content
[0155] Another indicator for determining the quality of fruit is the determination of fruit acid content. The test samples were determined by acid-base titration. The test steps are as follows: titratable acidity is determined by titrating the strawberry solution with the prepared sodium hydroxide solution. That is, at room temperature, 10g of ground strawberry sample was rinsed into a 50mL conical flask and shaken to volume. The solution was decolorized with 0.4g kaolin per gram of sample, and the supernatant was taken after centrifugation (6000r, 10min), and the sample solution was obtained by filtering with filter paper; then phenolphthalein indicator was added to the sample solution, and titrated with NaOH solution, and the amount of NaOH solution used was recorded. Each group of tests was repeated three times. This method was used to perform 5 blank control tests with distilled water, and the results were averaged. The titratable acid content was calculated according to malic acid (0.067g / mol). The calculation formula is as follows:
[0156]
[0157] Wherein: TA is the titratable acid content; V is the total volume of the sample extract, mL; C is the concentration of the NaOH titrant, mol / L; V1 is the volume of the NaOH solution consumed in the titration of the sample filtrate, mL; V0 is the volume of the NaOH solution consumed in the titration of the distilled water, mL; F is the conversion factor, g / mmol; Vs is the volume of the filtrate taken during titration, mL; m is the sample mass, g.
[0158] (8) Determination of ascorbic acid content
[0159] Ascorbic acid content is the Vc content. The Vc content in fruits is one of the important indicators for evaluating the nutritional value of the fruit. Some consumers will decide whether to consume the fruit based on the Vc content of the fruit. Therefore, it is necessary to measure the ascorbic acid content of preserved fruits. This test refers to the method of GB5009.86-2016 "Determination of Ascorbic Acid in Foods" and uses the 2,6-dichloroindophenol titration method for experimental research.
[0160] Standardize 2,6-dichloroindophenol solution: prepare a 50mL conical flask for use, transfer 1mL ascorbic acid (1mg / mL) solution and 10mL oxalic acid (1%) solution into it and mix well, add a certain amount of 2,6-dichloroindophenol solution for titration. The calculation formula for the amount of 2,6-dichlorophenol solution added is as follows:
[0161]
[0162] Where: T is the titration degree, that is, the mass of ascorbic acid equivalent to each milliliter of 2,6-dichloroindophenol solution, mg / mL; C is the mass concentration of ascorbic acid standard solution, mg / mL; V is the volume of ascorbic acid standard solution absorbed, mL; V1 is the volume of 2,6-dichloroindophenol solution consumed by titrating ascorbic acid standard solution, mL; V0 is the volume of 2,6-dichloroindophenol solution consumed by titrating blank, mL;
[0163] Test steps for strawberry samples: Put 10g of strawberry samples in different packaging methods into an agate mortar, then add 20mL of 2% oxalic acid solution and grind it into a uniform paste. Then take a 100mL volumetric flask, filter it in with multiple layers of gauze, rinse the mortar and gauze with oxalic acid and put them into the volumetric flask, and dilute the volume of the volumetric flask to 100mL. Add kaolin to decolorize the solution, the addition ratio is 0.4g kaolin per gram of sample, and then filter to obtain the sample solution. Use 2,6-dichloroindophenol to calibrate the sample solution for titration test. And do a blank control. Each group of tests should be repeated at least 3 times, and the results are averaged. The calculation formula for ascorbic acid content is as follows:
[0164]
[0165] Wherein: X is the ascorbic acid content in the sample, mg / 100g; V is the total volume of the extract, mL; V1 is the volume of 2,6-dichloroindophenol solution consumed by titrating the sample, mL; V0 is the volume of 2,6-dichloroindophenol solution consumed by titrating the blank, mL; T is the titer of 2,6-dichloroindophenol solution, that is, the number of milligrams of ascorbic acid per milliliter of 2,6-dichloroindophenol solution, mg / mL; Vs is the volume of the sample solution taken during titration, mL; m is the mass of the strawberry sample.
[0166] (9) Determination of malondialdehyde (MDA) content
[0167] This test was conducted with reference to the method of GB5009.181-2016 "Determination of malondialdehyde in food". 3mL of trichloroacetic acid and 1g of strawberry sample were placed in an agate mortar and ground evenly, then the mortar was rinsed with 7mL of 10% trichloroacetic acid, and the above solutions were combined and mixed evenly; the supernatant was centrifuged and mixed with the same volume of thiobarbituric acid solution and cooled in a boiling water bath before centrifugation again. The absorbance of the supernatant was measured at wavelengths of 450, 532 and 600nm, respectively, and the test was repeated 3 times. The formula for calculating the malondialdehyde content is as follows:
[0168] MDA concentration 6.45×(OD532-OD600)-0.56×OD450
[0169] Amount of MDA = MDA concentration x total volume of extract x fresh weight of plant tissue
[0170] Wherein: OD532 is the absorbance of the supernatant at a wavelength of 532 nm; OD600 and OD450 are the same as above.
[0171] 4. Data processing
[0172] All experimental data were statistically processed by Microsoft Excel 2016 software, and SPSS Statistics 26 and Origin 2019b were used for statistical analysis and graphing. All parallel experiments were repeated 3 times or more, and the results were taken as the experimental average. When the experimental results were P < 0.05, there was a significant difference.
[0173] Appearance changes and decay degree of strawberries packaged in CK group, PE group, coating group and film group before storage and after 7 days of storage. Fig.14 As the storage time goes by, accompanied by the action of microorganisms, oxidation, respiration, enzymes, etc., the nutrients in the strawberry decompose and change, the color, shape, taste, etc. of the strawberry change, the sensory evaluation shows a downward trend, and the nutritional value is lost. Fig.14 It can be seen that both packaged and unpackaged strawberries rotted. Compared with the unpackaged samples, the discoloration and rot of the packaged strawberries were less severe, which shows that the coated group and the coating group can maintain the freshness of the strawberries. The preservation effect of the CK group was poor. Among the strawberries that were not fully mature, the CK group and the PE group were fully mature on the second day of storage. On the third day, the CK group and the PE group had already been contaminated with bacteria and mold, while the coating group and the coating group did not have this phenomenon. This also shows that the coating group and the coating group can inhibit microbial contamination to a certain extent. The invasion of bacteria first caused the death of some cells in the strawberry, weakened the strawberry's own defense system, and reduced its ability to resist external mold. The strawberries invaded by bacteria provided soil for the growth of mold and other microorganisms. After the fifth day of storage, the CK group and the PE group had lost their commodity value. The sensory picture of the strawberries that were not rotten and deteriorated in the PE group was better than that of the CK group, because the PE group had a moisturizing effect. After five days of storage, the coating group also had mold spots, which may be due to the large amount of water in the coating group. The preservation effect of the coating group was better than the other three groups at this time. After seven days of storage, the preservation effects of the four groups were significantly different. The above results show that the CK group has no isolation effect, which makes the strawberries directly contact with microorganisms in the air and become contaminated; the PE group has a water-collecting effect, which accelerates the mildew of the strawberries and damages the fruit itself; the coating group has the effect of isolating microorganisms, but there is water in the film liquid, which makes the strawberries’ preservation effect not long; and the coating group can isolate microbial contamination and has a breathable effect, slowing down the respiration intensity of the strawberries and prolonging the preservation effect of the strawberries.
[0174] The thin skin of strawberries leads to rapid water loss and fruit shrinkage. The migration of water from the fruit to the environment exacerbates the decay of the strawberries. The high respiration rate and carbon dioxide migration from the skin lead to the above results. Fig.15 The weight loss effect of strawberries during storage is shown. The weight of strawberry samples under different packaging continued to decrease with the extension of storage time, and the difference between treatments was significant (p≤0.05). During storage, the PE group had the smallest weight loss due to its moisturizing effect, but because it was isolated from the air, the opposite of a good moisturizing effect was that it was easy to spoil due to excessive moisture; the control group without any treatment also showed an increasing weight loss over time; the film group and the coating group had a smaller water vapor permeability and a barrier effect on microorganisms, so they could act as a semi-permeable barrier to prevent moisture and gas, thereby reducing the respiration rate and weight loss, so the weight loss was smaller.
[0175] The respiration of fruits is closely related to the consumption of products. Respiration is an important physiological activity after fruits are picked. One of the ways to preserve fruits after they are picked is to inhibit their respiration during the ripening process. The stronger the respiration of the fruit, the shorter its storage period, the more restricted the quality assurance, and the faster the loss of nutrients inside the fruit; conversely, by inhibiting the respiration rate of fruits and vegetables and their oxidation process, reducing the consumption of organic matter, the spoilage process of the fruit can be slowed. During the storage period after picking, the quality of fruits and vegetables is directly related to the strength of their respiration. Therefore, to preserve fruits and vegetables, an important point is to inhibit their respiration, but not to affect the normal consumption of the fruit, so as to achieve the purpose of food preservation. Fig.16 It was found that the respiration of strawberries increased with the extension of storage time. The respiration intensity of freshly picked strawberries was gentle, and the respiration was low at this time. With the extension of storage time, when stored for the 4th day, its respiration intensity tended to be saturated and the strawberry samples began to mold due to the excessive consumption of nutrients. When stored for the 5th day, the respiration intensity of strawberry samples in different packaging states was stable, and the respiration intensity showed different growth trends with different degrees of decay. The respiration intensity of strawberry samples under coating and film coating conditions during the entire storage process was lower than that of the control group, indicating that the Bletilla striata polysaccharide composite film or composite coating liquid of the present invention can effectively delay the respiration of strawberries.
[0176] During storage, the organic acids in strawberries are constantly consumed due to respiration, which affects the sensory, flavor and quality of strawberries. The remaining value of the nutrients in strawberries can be seen by testing the pH value of strawberry pulp. The test results are shown in Table 7. The enzymatic reaction of sugars produced by strawberry ripening will be affected as the storage period increases, the amount of acid will decrease, and the pH value will increase. The organic acid content of strawberries in different packages during storage: CK group>PE group>coating group>encapsulated group. The reason is that compared with the blank control group, the coating or encapsulation of Bletilla striata polysaccharide inhibits the air flow on the surface of the strawberry, reduces the consumption of organic acids to a certain extent, prolongs the ripening time, increases the shelf life of strawberries, and increases its economic value. The preservation effect of the PE group is not obvious. It may be that during the storage process, PE preservation will produce excess water, thereby accelerating the decay and deterioration of strawberries, which is not conducive to maintaining the organic acid content in strawberry fruits. As the storage time goes by, the pH value of strawberries in different packages gradually increases, which is consistent with previous studies. This indicates that the composite film or the prepared coating liquid with good mechanical properties and low water vapor permeability can effectively inhibit the increase of pH value of strawberries and prolong the storage period of strawberries.
[0177] Table 7
[0178]
[0179] Soluble solids content is one of the parameters studied for fruit quality and consumer acceptance. Fruit maturity and metabolic reactions increase the sugar level in the fruit and are factors that affect TSS content during storage. Fig.17 It can be seen that the changes in the total soluble solids (TSS) content of strawberries with different packaging treatments within 5 days of storage were studied. It can be seen that during the storage period, the TSS of all treatments remained stable (p>0.05). With the extension of storage time, the disappearance of nutrients such as sugar, acid, and vitamins in strawberries caused the TSS content to decrease. Mitcham reported that the change in TSS of strawberries may be related to the conversion of starch into sugar or anthocyanin content. Through this conversion, the amount of sugar and soluble solids increases. Compared with strawberry samples in other packages, the TSS of strawberries in the coated or film-coated groups decreased slowly, indicating that the composite film with the addition of Bletilla striata polysaccharide can slow down the deterioration of fruits and vegetables to a certain extent.
[0180] Organic acid is another important property of strawberries, which is significantly affected by metabolic rates such as respiration. Fig.18As shown. The TA values of all packages decreased during storage, which may be due to the increased maturity during storage and the consumption of organic acids in basic metabolic reactions. Compared with the samples in the CK group and the PE group, the decline rate of TA content in the packaged strawberries in the film-coated group and the coating group was lower during storage. This is because the low-oxygen environment caused by the film composed of RBP / SA / CMC hindered the diffusion of oxygen molecules, thereby inhibiting the respiration rate and acid metabolism. This result indicates that the Bletilla striata polysaccharide composite film of the present invention can delay the consumption of organic acids, thereby extending the shelf life of fruits.
[0181] Vitamins and minerals are part of the important nutrients in vegetables and fruits, and ascorbic acid (vitamin C) is particularly prominent. Ascorbic acid is beneficial to human health and is a cofactor for many enzymatic reactions. However, it is easily oxidized when exposed to heat, light, and oxygen conditions. From Fig.19 It can be seen that the ascorbic acid content of strawberries with different packages gradually decreased over time, which is consistent with the decline in eating quality. The decrease in the ascorbic acid content in strawberries is due to the increased maturity and the degradation of fruit tissues. The ascorbic acid content of packaged strawberries is higher than that of unpackaged strawberries, indicating that all films effectively inhibited the loss of ascorbic acid in packaged strawberries. Due to its good oxygen barrier performance, the Bletilla striata polysaccharide composite film can act as a strong barrier to inhibit the oxygen exchange between strawberries and the external environment, form a lower oxygen atmosphere, slow down the respiration rate, and thus delay the deterioration of ascorbic acid. Therefore, the Bletilla striata polysaccharide composite film of the present invention can effectively maintain the content of ascorbic acid.
[0182] The content of malondialdehyde (MDA), as one of the products of membrane lipid peroxidation, is an important indicator to measure membrane lipid peroxidation. During the post-ripening and senescence of fruits and vegetables, as well as during mechanical damage, due to the continuous increase in the content of antioxidant enzymes inside their tissues, the MDA content inside strawberries increases. From Fig. 20 As shown, during the entire storage process, the MDA content in the blank group increased the fastest, and the MDA content of strawberries with different packages showed an upward trend. The rule is as follows: coating group < film-coated group < PE group < CK group. The MDA content in the film-coated group and the coating group was alleviated compared with the PE group, probably because the Bletilla striata polysaccharide in the film-forming material has certain antioxidant properties. After 6 days of storage, the quality of the strawberries in the control group has deteriorated, the fruits are no longer fresh, and they no longer have storage value. However, both the Bletilla striata polysaccharide composite film and the Bletilla striata polysaccharide composite coating solution of the present invention can slow down the growth of MDA content during the preservation of strawberries, thereby increasing the storage period of strawberries to a certain extent.
[0183] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a Bletilla striata polysaccharide composite film, characterized in that: The following steps are involved: Step 1, preparing Bletilla striata powder; Step 2, preparing Bletilla striata polysaccharide; Step 3, dissolving Bletilla striata polysaccharide, sodium alginate and sodium carboxymethyl cellulose in deionized water respectively, stirring in a water bath, to prepare Bletilla striata polysaccharide solution, sodium alginate solution and sodium carboxymethyl cellulose solution respectively; Step 4: Evenly mix the three solutions obtained in step 3 to obtain a mixed solution, then add glycerol, stir in a water bath, and after ultrasonic degassing, pour the obtained film-forming solution into a mold and evenly cast it. After drying, peel off the film to obtain a Bletilla striata polysaccharide composite film.
2. The method for preparing a Bletilla striata polysaccharide composite film according to claim 1, characterized in that: In the step 1, the preparation method of the Bletilla striata powder is as follows: the root tubers of the Bletilla striata are washed, frozen at -15 to -20°C for 3 to 6 hours, and then the root tubers of the Bletilla striata are crushed at a crushing temperature of -15 to -20°C and a pressure of 0.1 to 0.3 MPa, spray dried, and passed through a 100-mesh sieve to obtain the Bletilla striata powder.
3. The method for preparing a Bletilla striata polysaccharide composite film according to claim 1, characterized in that: In the step 2, the preparation method of Bletilla striata polysaccharide is as follows: add Bletilla striata powder into pure water, stir at 70-90°C and 300-600rpm for 1-2h, then centrifuge at 2000-4000rpm for 8-15min, collect the supernatant, add the remaining insoluble residue into pure water again, stir and centrifuge twice, combine the supernatants collected three times, evaporate and concentrate in a water bath, then add 2-4 times the volume of 95% ethanol, stir into flocs and let stand at 2-6°C for 10-14h, then centrifuge at 4000-6000rpm for 8-15min, collect the precipitate, freeze it for 10-14h, then freeze-dry it, and crush it at 10000rpm for 3min to obtain Bletilla striata polysaccharide.
4. The method for preparing a Bletilla striata polysaccharide composite film according to claim 3, characterized in that: The mass volume ratio of the Bletilla striata powder to pure water is 3-6 g:100-300 mL; the water bath temperature is 50-60° C., and the volume is evaporated and concentrated to 1 / 10-2 / 5.
5. The method for preparing a Bletilla striata polysaccharide composite film according to claim 1, characterized in that: In the step 3, the concentration of the Bletilla striata polysaccharide solution is 1.4-1.6 wt %; the concentration of the sodium alginate solution is 1.0-1.2 wt %; and the concentration of the sodium carboxymethyl cellulose solution is 1.2-1.6 wt %.
6. The method for preparing a Bletilla striata polysaccharide composite film according to claim 1, characterized in that: In the step 3, the stirring temperature in the water bath is 50-70° C. and the stirring time is 1-3 h.
7. The method for preparing a Bletilla striata polysaccharide composite film according to claim 1, characterized in that: In the step 4, the amount of glycerol added is 0.5-1.0 wt% of the mixed solution; the temperature of the water bath stirring is 50-70° C., and the time is 20-40 min; the drying temperature is 50-60° C., and the time is 20-30 h.
8. A Bletilla striata polysaccharide composite film, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of a Bletilla striata polysaccharide composite film prepared by the preparation method according to any one of claims 1 to 7 in inhibiting Escherichia coli and Staphylococcus aureus.
10. Use of the Bletilla striata polysaccharide composite film prepared by the preparation method according to any one of claims 1 to 7 in preserving strawberries.
